Pathophysiology : concepts of altered health science - Porth, Carol Mattson (Philadelphia, Pennsylvania : J.B. Lippincott Company, 1994)
Prepare your students for their future careers with Essentials of Pathophysiology: Concepts of Altered Health States, 4/e. This clear, readable, and student-friendly text delivers (3z(Bneed to know(3y (Bdisease content, along with the essential foundation in science that nursing, physician assistant, pharmacology, advanced health science, and medical students need to succeed in their future careers. Approaching the topic as an exploration of pathophysiology, the book relates normal body functioning to the physiologic changes that occur as a result of disease and provides concise yet complete coverage of how the body works. The Fourth Edition builds on the book$1 (Bs extremely successful art program and the (3z(BUnderstanding(3y (Bfeature and incorporates summary concept boxes after each section. In addition, an expanded, robust, and flexible suite of supplements, including a Study Guide, over 40 advanced 3-D animations, PrepU, and Lippincott$1 (Bs CoursePoint , provide students with all the tools they need to succeed.s
Unit I. Alternations in Cell Function and Growth -- Unit II. Developmental Aspects of Altered Health -- Unit III. Alterations in Integrated Body Function -- Unit IV. Alterations in Body Defenses -- Unit V. Alterations in Oxygenation of Tissues -- Unit VI. Alterations in Fluids and Electrolytes -- Unit VII. Alterations in Genitourinary Function -- Unit VIII. Alterations in Metabolism, Endocrine Function, and Nutrition -- Unit IX. Alterations in Neuromuscular Function -- Unit X. Alternations in Skeletal Support and Movement
Includes bibliographical references and index.
Keywords: PHYSIOLOGY, PATHOLOGICAL